The clownfish-hosting sea anemones (Anthozoa: Actiniaria): updated nomenclature, biogeography, and practical field guide. - Titus, Benjamin M.; Bennett-Smith, Morgan F.; Chiodo, Tommaso; Rodríguez, Estefanía (Zootaxa, 2024)
Ten described species of sea anemones (Anthozoa: Hexacorallia: Actiniaria) serve as hosts to charismatic clownfishes (or anemonefishes) on coral reefs throughout the tropical Indo-West Pacific. Although not diverse in number, the clownfish-hosting sea anemones have large biogeographic ranges, exhibit extensive intraspecific phenotypic appearances, and have been surrounded by a great deal of historical and contemporary taxonomic and nomenclatural confusion. We believe these factors have created challenges for field scientists making real-time species-level identifications of host sea anemones. Subsequently, a surprising amount of peer-reviewed clownfish literature never accounts for the host sea anemone, omitting critical data for understanding the symbiosis ecologically and evolutionarily. Here, we leverage the revolution that has taken place in the realm of digital underwater photography over the past 30 years to provide an updated, practical field guide for the clownfish-hosting sea anemones. First however, we review and revise the nomenclature for each species to better reflect valid changes that were made in the historical literature but never broadly adopted. Next, we demonstrate that machine learning algorithms may be of limited use for automating sea anemone species IDs from digital photographs alone—highlighting the importance of organismal expertise for identifying these animals. Finally, we present high-resolution digital photographs that encompass much of the intraspecific phenotypic variation encountered underwater, discuss important characteristics useful for field IDs, and provide updated range maps for each species to better reflect the known biogeographic range of each host anemone. We hope the increased confidence in field identification provided by this guide will result in more papers incorporating the sea anemone host data into research frameworks and subsequent publications.